Healthcare-associated infections and antimicrobial use in long-term care facilities (HALT3): an overview of the Italian situation. Issue 4 (August 2019) - ,; Moro, Maria Luisa; Brusaferro, Silvio; Sticchi, Camilla; Chadenier, Giulia Marie; D'Errico, Marcello; Ripabelli, Giancarlo; Prato, Rosa; Mura, Ida Iolanda; Agodi, Antonella; Collini, Francesca; Torri, Emanuele; et al.
Summary: Background: Awareness of healthcare-associated infections (HAIs) and antimicrobial use in long-term care facilities (LTCFs) is increasing. In 2017, the third national point prevalence survey (PPS) was conducted in Italy as part of the third 'Healthcare-Associated Infections in European Long-Term Care Facilities' (HALT3) study. Aim: To report the results of HALT3 and analyse the resident population of LTCFs, implementation of good practices, prevalence of infections and antimicrobial use. Methods: The survey was designed as a PPS, carried out from April to June 2017. All residents who lived full-time in the institution were included. All facilities were asked to complete an institutional questionnaire, a ward list for all residents, and a resident questionnaire for those residents presenting with signs/symptoms of active infection and/or receiving an antimicrobial agent. Findings: In total, 418 facilities took part in the study; 24, 132 residents were eligible, and most were aged >85 years, disoriented and incontinent. The prevalence of HAIs was 3.9%, and 50% of the institutions reported that they had a professional trained in infection control on their staff. Only 26.4% of infections were confirmed by a microbiological sample, and 26.9% of the isolated micro-organisms were resistant to at least one antimicrobial class. In total, 1022 residents received at least one antimicrobial agent, and cephalosporins were prescribed most commonly. Conclusion: The number of infection control and antimicrobial stewardship measures implemented was found to be considerably higher in this study compared with previous studies. This could lead to a reduction in the prevalence of HAIs, antimicrobial use and antimicrobial resistance. Further studies are needed to monitor these aspects.